Hypoxia induces universal but differential drug resistance and impairs anticancer mechanisms of 5-fluorouracil in hepatoma cells - Li, Jing-qiu; Wu, Xian; Gan, Lu; Yang, Xiang-liang; Miao, Ze-hong (Acta pharmacologica Sinica, 2017)
Hepatocellular carcinoma （HCC） is one of the most refractory cancers. The mechanisms by which hypoxia further aggravates therapeutic responses of advanced HCC to anticancer drugs remain to be clarified. Here, we report that hypoxia （1% 02） caused 2.55-489.7-fold resistance to 6 anticancer drugs （sorafenib, 5-fluorouracil [5-FU], gemcitabine, cisplatin, adriamycin and 6-thioguanine） in 3 HCC cell lines （BEL-7402, HepG2 and SMMC-7721）. Among the 6 drugs, sorafenib, the sole one approved for HCC therapy, inhibited proliferation with little influence from hypoxia and displayed the smallest variation among the 3 HCC cell lines tested By contrast, the inhibition of proliferation by 5-FU, which has been extensively tested in clinical trials but has not been approved for HCC therapy, was severety affected by hypoxia and showed a large variation among these cell lines. In 5-FU-treated HCC cells, hypoxia reduced the levels of basal thymidylate synthase （TS） and functional TS, leading to decreased dTMP synthesis and DNA replication. Hypoxia also affected the accumulation of FdUTP and its misincorporation into DNA. Consequently, both single-strand breaks and double-strand breaks in DNA were reduced, although hypoxia also inhibited DNA repair. In 5-FU-treated HCC cells, hypoxia further abated S-phase arrest, alleviated the loss of mitochondrial membrane potential, diminished the activation of caspases, and finally resulted in reduced induction of apoptosis. Thus, hypoxia induces universal but differential drug resistance. The extensive impacts of hypoxia on the anticancer mechanisms of 5-FU contributes to its hypoxia-induced resistance in HCC cells. We propose that hypoxia- induced drug resistance and interference of hypoxia with anticancer mechanisms could be used as candidate biomarkers in selecting and/or developing anticancer drugs for improving HCC therapy.